Mesolithic interfaces : variability in lithic technologies in Eastern Fennoscandia [Review] - Čuláková, K. (Katarína)
Book is a good base for a discussion about Mesolithic lithic technologies and raw materials sources. Authors are working with material in really fruitfull way. In every chapter first is material presented in attentive way, and then theoretic concept comes.